Systems Analysis: A Computer Approach to Decision Making (Book). - Davis, Edward W.; Sterling, Robert R. (The Accounting Review, 1970)
Reviews the book "Systems Analysis: A Computer Approach to Decision Models," by Claude McMillan and Richard F. Gonzalez.